2006
DOI: 10.1270/jsbbs.56.131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-molecular-weight and Low-molecular-weight Glutenin Subunit Alleles on Common Wheat Flour Quality

Abstract: To elucidate the effects of different glutenin subunit alleles on the parameters of wheat flour quality, we analyzed the dough and gluten properties using a doubled-haploid population derived from a cross between two wheat cultivars differing in the glutenin subunit loci except for Glu-D3, namely Grandin (Glu-A1b, Glu-B1c, Glu-D1d, Glu-A3f, Glu-B3h and Glu-D3a) and Kitamiharu 57 (Glu-A1a, Glu-B1i, Glu-D1a, Glu-A3c, GluB3b and Glu-D3a). Based on the analysis of the DH lines, no significant differences in the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 23 publications
4
11
0
1
Order By: Relevance
“…Thus, our results agreed with some studies but differed from others. For example, at the Glu-A1 locus, the alleles Glu-A1a and b were reported to have similar quality in some studies Tabiki et al 2006). In our study, Glu-A1b was associated with higher (P \ 0.05) MPW than GluA1a (Table 4).…”
Section: Effects Of Glutenin Loci and 1al1rssupporting
confidence: 61%
“…Thus, our results agreed with some studies but differed from others. For example, at the Glu-A1 locus, the alleles Glu-A1a and b were reported to have similar quality in some studies Tabiki et al 2006). In our study, Glu-A1b was associated with higher (P \ 0.05) MPW than GluA1a (Table 4).…”
Section: Effects Of Glutenin Loci and 1al1rssupporting
confidence: 61%
“…Among Glu-B1 and Glu-D1 alleles, Glu-B1i and Glu-D1d showed strongest effects and negated the influence of alleles encoded at Glu-3 loci. Glu-A1b showed stronger effect on sedimentation volume and mixograph parameters as compared to Glu-A1a and c. Luo et al (2001) also reported stronger relationship of Glu-A1b allele, however, He et al (2005), Liu et al (2005), Figueroa et al (2009) and Tabiki et al (2006) suggested the stronger role of Glu-A1a in quality parameters. Surprisingly, there was no significant effect of Glu-B1 and Glu-D1 loci on mixograph mixing time, but variation at Glu-A1 significantly influenced mixing time.…”
Section: Effect Of Hmw and Lmw Glutenins On Sedimentation Volume And mentioning
confidence: 81%
“…These discrepancies may be due to the difference in the genetic background of the cultivars used. There are very few reports of the effect of Glu-D3 locus and its allelic variant on quality parameters Tabiki et al 2006;Maucher et al 2009). In this study, we included the new Glu-D3 alleles identified through PCR based markers: Glu-D3 g, i and j. Glu-D3b and Glu-D3g exhibited stronger mixograph characteristics.…”
Section: Effect Of Hmw and Lmw Glutenins On Sedimentation Volume And mentioning
confidence: 99%
“…Several studies have been carried out to evaluate the effects of Glu-3 allelic variations on dough properties Eagles et al 2001;Gupta et al 1994;Killermann and Zimmermann 2000;Maucher et al 2009;Metakovsky et al 1990). The interactive effects of Glu-1 and Glu-3 loci on flour and end-use quality have been also estimated since both HMW-GS and LMW-GS are useful genetic markers for quality improvement of wheat (Flaete and Uhlen 2003;He et al 2005;Kolster et al 1991;Liu et al 2005;Luo et al 2001;Nagamine et al 2000;NietoTaladriz et al 1994;Tabiki et al 2006;Zhang et al 2007Zhang et al , 2009.…”
Section: Introductionmentioning
confidence: 99%